2021
DOI: 10.1007/s00431-020-03915-x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac remodeling in patients with childhood-onset craniopharyngioma—results of HIT-Endo and KRANIOPHARYNGEOM 2000/2007

Abstract: Hypothalamic obesity caused by childhood-onset craniopharyngioma results in long-term cardiovascular morbidity. Knowledge about clinical markers and risk factors for cardiovascular morbidity is scarce. A cross-sectional study on transthoracic echocardiographic parameters was performed to determine the associations with clinical and anthropometric parameters in 36 craniopharyngioma patients. BMI correlated with the thickness of interventricular septum in diastole (IVSd) (r = 0.604, p < 0.001) and left ventri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 57 publications
0
8
0
1
Order By: Relevance
“…Long-term outcome after CP is frequently impaired by morbidity due to hypothalamic obesity including cardiovascular (26) and neurovascular disease (27). Neurovascular complications such as CI in CP may result from injury to any of the major intracranial vessels and their branches, due to tumor location/infiltration and/or treatment-related lesions such as surgical injury, postoperative vasopasms or XRT-induced vessel damage.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term outcome after CP is frequently impaired by morbidity due to hypothalamic obesity including cardiovascular (26) and neurovascular disease (27). Neurovascular complications such as CI in CP may result from injury to any of the major intracranial vessels and their branches, due to tumor location/infiltration and/or treatment-related lesions such as surgical injury, postoperative vasopasms or XRT-induced vessel damage.…”
Section: Discussionmentioning
confidence: 99%
“…One study comparing childhood- and adult-onset CP assessed the CVD risk, showing that adult-onset CP patients have a higher CVD risk than childhood-onset CP patients [ 23 ]. Multiple exposures were investigated: metabolic syndrome (MetS)/obesity [ 24 , 25 ], hypothalamic involvement (HI) [ 26 , 27 ], and growth hormone substitution therapy [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…In their studies, Jung et al demonstrated that MetS and HI led to cardiac autonomic dysfunction, increasing the risk of cardiovascular events in CP patients [ 24 , 27 ]. In a multicenter cohort study of childhood-onset CP patients, a higher degree of obesity was correlated with increased left ventricular wall thickness [ 25 ]. Holmer et al found that not only was HI an important risk factor for CVD in CP patients, but female CP patients were also at a higher risk of experiencing a CVD event [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the related literature reports, the incidence of various hormone defects in patients with craniopharyngioma is slightly different. We searched PubMed for keywords such as craniopharyngioma, endocrine, and hormone, and the subjects were identified as children or adults, and 11 related literatures (2,8,10,11,14,20,(49)(50)(51)(52)(53) were obtained. We sorted out the literature to find out the incidence of endocrine dysfunction in craniopharyngioma (Table 1).…”
Section: Pituitary Hormone Deficiencymentioning
confidence: 99%